Elaboración de un plan de marketing para fortalecer la captación de prospectos de estudiantes del programa de ingeniería civil de la Fundación Universitaria Juan de Castellanos (Tunja – Boyacá). - Rubio Reyes, Tatiana Paola (Universidad Antonio Nariño, 2022)
The project involves the preparation of a marketing plan for the civil engineering program of the Fundación Universitaria Juan de Castellanos, which will increase the number of students in the program.